Early Career Experiences and Later Career Outcomes: Comparing the United States, France and Germany - David N. Margolis; Véronique Simonnet; Lars Vilhuber (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper explores the links between individuals' early career experiences and their labor market outcomes 5 to 20 years later using data from France, (western) Germany, and the United States. Relative to most of the literature, we consider a large set of measures of men's early career experiences and later career outcomes. Our results differ significantly across countries. Labor market outcomes in Germany are consistent with a dual labor market model. In the case of American workers, either the market learns about unobservable worker characteristics over time or the implicit contracts established at the start of the career are increasingly renegotiated over time. Unobserved heterogeneity in individuals' networks of labor market contacts is consistent with our results for France. These results reflect optimal firm responses to the different institutional environments in each country in the presence of ex ante imperfect informationconcerning young workers.
Keywords: 330; Arbeitsmobilität; Erwerbsverlauf; Arbeitsmarktsegmentation; Bildungswesen; Vergleich; USA; Frankreich; Deutschland